PENGARUH PROFITABILITAS, JUMLAH DEWAN KOMISARIS DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi pada Industri Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2017) - DIO ARDIAN PRATAMA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The purpose of this study is to understand and explain the effect of profitability, number of board of commissioners and company size on corporate social responsibility disclosure. Determination of samples using purposive sampling method and obtained 46 companies as samples of mining industry sector which listed by IDX, period 2016-2017. This study using multiple regression method analysis. The results showed that profitability and company size have significant positive influence to corporate social responsibility. At the same time, number of board of commissioners have significant negative influance to corporate social responsibility. The results of this study is expected to be a guide for the management of the company by looking at the impact of disclosurecorporate social responsibility, and can be used as reference materials for further researchKeywords: profitability, number of board of commissioners, company size and corporate social responsibility.